Extrapolación psicológica infundada y su censura paradójica: Estudio de un lugar común plautino - Martín Rodríguez, Antonio María (1999)
The world of Plautinian comedy is governed by deceit and mistakes, which forces characters to believe only in what they see with their own eyes and in what they are able to learn from their own experience. Relying only on his experiences, however, the speaking subject may at times extrapolate into his listener characteristics that the latter will in no way recognize as his own. This extrapolation which in truth pertains to the receptor's interpretation, rather than to the speaker's intention, results in acerbic criticism from the listener.
Keywords: Plauto, Tito Maccio; Comedia; Mujeres